STUDY OF CORRELATION OF CHICKEN EGGS PRODUCTION TO CALORIE CONSUMPTION AND PREVALENCE OF POOR NUTRITION TO CHILDREN (0-59 MONTHS): COMMUNITY SERVICE SURVEY - Fajar Fatriansyah, Jaka; Febrian Pradana, Agrin; Egan Jonatan, Ignatius; Federico, Andreas; Yuriansyah Barmaki, Muhammad Joshua; Fauzi, Andrian; Rohman, Muhammad Syaikh (LPPM Univ. Ibn Khaldun Bogor, 2022)
Indonesia is a country with low consumption of chicken eggs and this has implications for the high prevalence of malnutrition among children under five in Indonesia. In this community service survey research, an analysis of the correlation between chicken egg production and calorie consumption will be carried out as the prevalence of under-five malnutrition (0-59 months). The analysis carried out is Pearson correlation analysis. The study found that there was a positive correlation between egg production per capita and egg consumption per province with a correlation coefficient of 2.067 x 103 tons/kcal. In addition, there is also a negative correlation between egg consumption and the prevalence of malnutrition in children under five (0-59 months). This study obtained a recommendation that it is important to increase egg production by increasing the productivity of chicken egg SMEs in the community service scheme.